The effects of sulfur-containing compounds on total antioxidant capacity levels of liver, kidney and brain in lead-exposed rats - Caylak, Emrah; Halifeoglu, Ihsan; Aydin, Sueleyman; Telo, Selda; Bulmus, Oezguer; Celik, Hakim (Ortadogu Ad Pres & Publ Co, 2007)
Objective: Lead is a non-essential toxic heavy metal widely present in the environment and chronic exposure to has been a matter of public health concern in many countries. Considering the sulfur-containing compounds with antioxidant activity to prevent or treat experimental lead toxicity in animals, this study was carried out to investigate the antioxidative effects of some sulfur-containing compounds in rats where oxidative stress was induced by lead acetate. Material and Methods: Wistar albino rats were exposed to 2000 ppm of lead, as lead acetate, alone or with daily to sulfur-containing compounds [L-methionine, lipoic acid (LA), N-acetylcysteine (NAC), L-homocysteine (Hcy)] for five weeks. The parameters of oxidative stress, and the levels of total antioxidant capacity (TAC) were determined [malondialdehyde (MDA) in sera by Satoh-Yagi's method; TAC in liver, kidney and brain by ABTS* method] in rats following the experiment (Analysis of the data was performed by one-way analysis of variance (ANOVA) and subsequent analysis was performed using the Tukey test. In lead group MDA levels in sera were determined to be significantly high compared to controls (p< 0.01)]. Results: In lead group MDA levels in sera were determined to be significantly high compared to controls (p< 0.01). MDA levels in sera were reduced in all groups compared to lead group (p< 0.01). In all lead-antioxidants groups liver TAC levels were determined to be slightly lower compared to lead group while brain's levels were higher. Kidney TAC levels in lead-methionine, and lead-LA groups were significantly high (p< 0.01). Conclusion: These results suggested the oxidative stress induced by lead was reduced, and the antioxidant capacities in lead-exposed rats were altered by sulfur-containing compounds.
19th National Biochemistry Congress of the Turkish-Biochemical-Society -- APR 22-25, 2005 -- Antalya, TURKEY
Keywords: lead; methionine; thioctic acid; acetylcysteine; homocysteine